الرقابة الادارية و دورها في تحسي الأداء الوظيفي دراسة ميدانية لدى موظفي مؤسسة الصندوق الوطني للتأمينات الاجتماعية للعمال الأجراء ببلدية الأغواط - محمد شلامة; زينب البار; سمية جقيدل (My University, 2023)
The study aimed to identify the control over the performance of employees of the National Social Security Fund, and the effectiveness of control methods and their achievement of the desired goals within the organization based on theoretical and applied projections of this work in order to reach some results that would raise the level of performance within the institution, Monitoring within the institution and frequent and sudden visits to the official and not pressuring the worker lead to the regularity of the worker in his work and respect for the laws, which leads to the performance required of him in the best way, and the recognition of the institution's workers that control contributes to directing motivation and raising it for them, which indicates the prominent role of the monitoring process. The results of the study were: - The first hypothesis is that administrative control has a role in increasing the effectiveness of some employees of the Social Security Corporation in the municipality of Laghouat. - The second hypothesis is that administrative control has a role in improving production efficiency. - The third hypothesis is that administrative control has a role in the successful evaluation of performance. Keywords: Administrative control, job performance, employees of the institution